DTA-TG Analysis of Gd0.95La0.05Ba1.95Sr0.05Cu3Oy Compounds - Sumadiyasa, Made; Suardana, I Putu; Wendri, Nyoman (BULETIN FISIKA; Vol 21 No 1 (2020): BULETIN FISIKA, 2020)
The sintering temperature is played a vital role in the evolution of phase structure, microstructure, and the properties of the superconductor. In this study, the Gd 0.9 La 0.1 Ba 1.95 Sr 0.05 Cu 3 O 7- d phase compound has been synthesized by the wet method using HNO3 as a solvent. The samples were divided into two groups. The first sample was calcined at 400 °C for 2 hours + 500 °C for 2 hours + 600 °C for 6 hours. The second sample treated by the same process and then continued by heating at 900 °C for 15 minutes. The effect of the calcination temperature for the synthesis of Gd 0.9 La 0.1 Ba 1.95 Sr 0.05 Cu 3 O 7- d bulks was investigated using the DTA-TG method. The results showed that the optimum reaction temperature for the formation of Gd 0.9 La 0.1 Ba 1.95 Sr 0.05 Cu 3 O 7- d phase was 938 °C. The additional heating temperature e.g. 900 °C for 15 minutes on the calcination process can reduce the optimum formation temperature of Gd 0.9 La 0.1 Ba 1.95 Sr 0.05 Cu 3 O 7- d compounds by 20 °C. The peritectic melting reaction temperatures of the sample without the addition of heating and with the addition of heating at temperature 900 °C for 15 minutes are 1032°C and 1035°C, respectively. The melting temperatures of both samples are 1164 °C and 1200 °C.